Advances in Sulphonation Techniques Liquid Sulphur Dioxide as a Solvent of Sulphur Trioxide - Ashar, Navin G. (SpringerBriefs in Applied Sciences and Technology, 2016)
This book presents a complete, in-depth analysis for on the impact of liquid sulfur dioxide and liquid sulfur trioxide to carry out complex and difficult sulfonations, as well as manufacture of sulfuric acid with a CAPEX requirement of less than half, an area requirement less than one-third, and no emission of sulfur dioxide. The processes described in this volume represents an innovative approach relevant to the current manufacturing processes of sulfuric acid, sulfamic acid, para toluene sulfonic acid and other sulfonated product.